DASAR YURIDIS SOSIOLOGIS PENGESAHAN RUU NO 16 TAHUN 2019 TENTANG BATAS USIA MENIKAH BAGI LAKI-LAKI DAN PEREMPUAN - Wahyudi Setiawan; Khoirul Asfiyak; Nur Hasan (Jurnal Hikmatina, 2020)
AbstractBackground :marriage law number 16 year 2019 is the end result of the long dialogue of the Indonesia people regarding marriage law, wich has been carried out from 1950 to 2019 the purpose of the ratification of law number 16 of 2019 on marriages is to make social changes and foster marital behavior in the community,wich at that time tended to harm women and children, because of the number of underage marriages, ratification of law number 16 year 2019 concerning marriage can not be separated from law number 1 of 1974 concerning marriage in which the law is considered by a group of citizens as a law that discriminates against women because in article 300 the civil code states that children namely those aged 21 years, in the law childrens welfare law also states that children are those who are 18 years old, for this reason a group of citizens submitted a request for revision to the constitusional court (MK) so that the constitusional court gave an order to the House Of Representatives (DPR) to immediately revise the old marriage law to create a healthy marriage physically and spriritually.Keywords: Background, yuridicial marriage, marriage law,discrimination